Shikonin Suppresses NLRP3 and AIM2 Inflammasomes by Direct Inhibition of Caspase-1 - Zorman, Jernej (PLoS One, 2016)
Shikonin is a highly lipophilic naphtoquinone found in the roots of Lithospermum erythrorhizon used for its pleiotropic effects in traditional Chinese medicine. Based on its reported antipyretic and anti-inflammatory properties, we investigated whether shikonin suppresses the activation of NLRP3 inflammasome. Inflammasomes are cytosolic protein complexes that serve as scaffolds for recruitment and activation of caspase-1, which, in turn, results in cleavage and secretion of proinflammatory cytokines IL-1β and IL-18. NLRP3 inflammasome activation involves two steps: priming, i.e. the activation of NF-κB pathway, and inflammasome assembly. While shikonin has previously been reported to suppress the priming step, we demonstrated that shikonin also inhibits the second step of inflammasome activation induced by soluble and particulate NLRP3 instigators in primed immortalized murine bone marrow-derived macrophages. Shikonin decreased NLRP3 inflammasome activation in response to nigericin more potently than acetylshikonin. Our results showed that shikonin also inhibits AIM2 inflammasome activation by double stranded DNA. Shikonin inhibited ASC speck formation and caspase-1 activation in murine macrophages and suppressed the activity of isolated caspase-1, demonstrating that it directly targets caspase-1. Complexing shikonin with β-lactoglobulin reduced its toxicity while preserving the inhibitory effect on NLRP3 inflammasome activation, suggesting that shikonin with improved bioavailability might be interesting for therapeutic applications in inflammasome-mediated conditions.